"What Will I Be Doing There Among So Many Women?": Perceptions on Male Support in Prevention of Mother to Child Services in Lilongwe, Malawi. (July 2019) - Nkhoma, Nicola; Nyondo-Mipando, Linda Alinane; Makanjee, Chandra; Myburgh, Nellie Dominica; Nyasulu, Peter Suwirakwenda
Participation of males in the prevention of mother-to-child transmission (PMTCT) programs remains a challenge despite the implementation of guidelines. The study aimed at exploring male involvement in the PMTCT program at a primary health facility in Lilongwe, Malawi. Focus group discussions and in-depth individual interviews were used to collect data from health care workers, men, and women who were attending PMTCT services. Snowball sampling was used to recruit participants who were purposively identified. Alcohol consumption, pressure from work places, stigma, role conflict, denial or nondisclosure of HIV status among women, and lack of awareness were among factors found to hinder male participation in PMTCT services. Therefore, to have an effective PMTCT program, male involvement is needed as this could positively influence the delivery of interventions including antiretroviral treatment among HIV-infected pregnant women. As such, health education awareness campaigns emphasizing the value of men in PMTCT services should be reinforced.